PENGEMBANGAN MEDIA VISUAL PADA MATERI JKW (JARAK, KECEPATAN DAN WAKTU) BAGI SISWA SEKOLAH DASAR KELAS VI - Ristika, Ristika; Elvadola, Connyta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop visual teaching aids on the topic of Distance, Speed and Time in Mathematics and Science lessons for Year 6 primary school pupils. This study employs a research and development (R&D) methodology comprising the stages of needs analysis, design, development, implementation and evaluation. Data collection techniques include observation, questionnaires and documentation. The research instruments consisted of an observation sheet to determine the responses of teachers and pupils, as well as an expert validation questionnaire. The results of the study showed that the expert validation of the material achieved a percentage of 84% in the ‘highly suitable’ category, whilst the expert validation of the media achieved a percentage of 94% in the ‘highly suitable’ category. Teachers’ responses to the use of the media showed a percentage of 86% in the ‘very practical’ category, and pupils’ responses achieved a percentage of 91% in the ‘very interesting’ category. Based on these results, it can be concluded that the literacy corner developed is suitable and beneficial for supporting and facilitating pupils’ understanding of JKW material in Mathematics and Science lessons at primary school.